SELF-CARE EDUCATION MASA MENSTRUASI PADA REMAJA - Nining Tunggal Sri Sunarti; Winarsih Winarsih (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Menstrual self-care education in adolescents Adolescent girls during menstruation require self-care such as hygiene, nutrition, rest patterns, exercise or physical activity. Efforts can be made to maintain reproductive health in women, namely by maintaining feminine hygiene during menstruation (Tarwoto and Watonah, 2010). Studies conducted on adolescents show that adolescents have the wrong knowledge about self-care so that they do the wrong self-care (Ibrahim et al., 2022) Based on research conducted by Anamika et al. (2008) on students found that premenstrual syndrome and dysmenorrhea were the most disturbing complaints. The purpose of this service is to increase knowledge about self-care during menstruation in adolescent girls. The method that will be used is the online lecture using the Zoom meeting media. The results obtained from this community service activity are increased knowledge about self-care during menstruation in adolescent girls. The results of the evaluation showed that there was an increase in knowledge about self-care during menstruation of participants before attending the webinar and after attending the webinar. It is necessary to carry out community service continuously as an effort to increase adolescent knowledge about health as an effort to improve the quality of life of adolescents Keywords: Menstrual self-care education, adolescents